Interpretation of Verbal and Visual Signs in the Converse Shoes Printed Advertisement - Putu Eka Yoga Aditya Pratama; Putu Gede Budiartha (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
Abstract This study, entitled